Kemampuan Pemecahan Masalah Pada Petugas Lembaga Pembinaan Khusus Anak Kelas I Kutoarjo - Galantino, Rizkia Monica; , Wisnu Sri Hertinjung, S. Psi, M, Psi (2016)
Wali is the official coaching institutions given additional duties as a surrogate parent for the students forged in the target institutions, while also accompanying all activities undertaken by the students and to help students when experiencing a problem. The purpose of this study is to understand the problem solving and the factors that influence the problem solving capabilities given by officers specialized coaching institutions grader I Kutoarjo. Researchers used a qualitative approach with four key informants and informant support 4. Key informants are personnel coaching institutions which became the guardian role as surrogate parent and mentor for guidance in institutions, while supporting informants are students who are in the target within the target institution. In this study, researchers used interview as a data collector.The results of this study indicate that each trustee has a way of melaukan troubleshooting. Wali having problems in guidance in the form of their leisure between the guardian with his protégé relationship trustee with the family, economic problems and in coaching, caregivers feel less have information or insights related to the field of psychology that is thought to help carers in a number of activities that involve students eg counseling when students are having problems. There are factors that support problem solving, namely higher education, work experience over 10 years and being a guardian over 3 years, the method of approach with students. In addition, there are factors inhibiting the provision of solutions that lower education, work experience under 10 years and a trustee under 3 years, the method of approach. These factors if done can influence problem solving capabilities will be provided.